DNA identification of compromised samples with massive parallel sequencing - Andreas Tillmar; Ida Grandell; Kerstin Montelius (Oxford University Press, 2018)
Genetic profiling is a standard procedure for human identification i.e. in criminal cases and mass disasters, and has been proven to be an important part in the process in the repatriation of victims to their relatives. In the event of a catastrophe whether it be a natural disaster, terror attack or accident, fatalities of many nationalities may be a consequence and international collaboration becomes necessary. Current DNA techniques used on a routine basis at forensic laboratories world-wide are very useful, and results reported from different labs are compared making it possible to be matched in order to declare the identification of a victim. Statistical calculations of possibilities of a random match are achievable since population data from many parts of the world is available. However, decomposition and degradation of the remains are not uncommon in the aftermath of a catastrophe and hence it may be difficult to retrieve detailed DNA profiles from such samples. Massive parallel sequencing (MPS) is a technique capable of producing a vast amount of DNA sequence data in a high through-put manner, and panels of Single Nucleotide Polymorphism (SNP) markers allow the amplification of small DNA fragments, often seen in compromised samples. Here, we report the results from a set of ten samples from missing person identification cases, analyzed with a MPS based method comprising 131 SNP markers and compared with direct reference material or buccal swab samples collected from relatives of the deceased. We assess the weight of evidence of a match by statistical calculation. Furthermore, we compare results reported on different platforms and using different SNP panels, and conclude that more work has to be done if results from missing person identification cases analyzed on MPS with SNP panels at different laboratories are to be fully reliable and thus comparable.